Metallothionein level in the larva of Cheumatopsyche sp. and the relationship between heavy metal concentration in Bone River, Gorontalo, Indonesia - Miftahul Khair Kadim; Endang Yuli Herawati; Diana Arfiati; ‪Asus Maizar Suryanto Hertika (Society for Indonesian Biodiversity, 2022)
Abstract. Kadim MK, Herawati FY, Arfiati D, Hertik AMS. 2022. Metallothionein level in the larva of Cheumatopsyche sp. and the relationship between heavy metal concentration in Bone River, Gorontalo, Indonesia. Biodiversitas 23: 5942-5950. This study aims to confirm that the larvae of Cheumatopsyche sp. contain a metal-binding protein, metallothionein, in their body and correlate it with heavy metal concentrations in the larval tissues and sediments in Bone River. Pb, Cd and Hg concentrations in sediment, tissue and Metallothionein (MT) levels were analyzed in several areas with different metal contamination. The Pb concentration in the sediment averaged 33.6 ppm; Hg 0.17 ppm; Cd 0.125 ppm. Total metals concentration in the whole body of Cheumatopsyche sp. ranged from 0.424 to 0.781, while the MT content ranged from 4637 to 6930 ng.g-1. The results revealed that the larvae could accumulate different metals and be more effective in accumulating Hg than Pb and Cd, regardless of the level of metal concentration in the sediment. Metal concentrations measured in Cheumatopsyche sp. showed a significant correlation with metals in the sediment. Metallothionein levels throughout the larval body showed differences in different areas of metal contamination and this correlated with the concentrations of Pb, Cd, and Hg measured in the larval tissue, thus reflecting their bioavailability in the environment. The results also showed that even under exposure to low metal concentrations, MT was still detectable in Cheumatopsyche sp. and proved to be a good predictor of metal accumulation.